Cost of Illness Analysis and Quality of Life in Ischemic Stroke Patients In Usu Medan Hospital - Saragih, Darma Ericson; Nasution, Azizah; K, Khairunnisa (Asian Journal of Pharmaceutical Research and Development, 2020)
Objective: aims to evaluate the COI INA-CBG BPJS patients hospitalized for ischemic stroke BPJS (n = 33) at USU Medan Hospital in February 2019-August 2019 period. Design: this study was conducted used a prospective cohort study method in patients with ischemic stroke (n = 33) in USU Hospital. Interventions: the intervened variable were the cost of patient therapy and calculating the difference in claims of INA-CBGs with the cost of patient therapy. Main outcome measures: the main measurement in this study was quality of life with European Quality of Life - 5 Dimensions Three Level (EQ5D3L). Results: the results of this study indicate the total average cost of ischemic stroke inpatient therapy at the In patient Installation of USU Hospital in Medan obtained Rp 2,284,854 The average cost / rate incurred by the Hospital for ischemic stroke patients (n = 33) is still below the INA-CBGs claim rate. There was a relationship between the quality of life of ischemic stroke patients with diagnosis and comorbidities of patients (p = 0.004). The average quality of life (QoL) of ischemic stroke patients was obtained 0.7324 ± 0.2118. Conclusion: it could be concluded that the quality of life of ischemic stroke patients is classified as good 32 patients (96.96%).